Technology Challenges and Opportunities in Indonesian School Education: Tantangan dan Peluang Teknologi dalam Pendidikan Sekolah Indonesia - Mali, Yustinus Calvin Gai; Tresiani, Ike; Harwanto, Novie Feronika; Renita, Reza; Putriani, Arlinda; Widiprastyanti, Anita; Yuntiawati, Meykke Alvia; Erinta , Elmi; Samsuar, Rizky Setiawan; Arya, Raynaldo Gusti; Setia, Narendra (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Technology has become an essential component in contemporary education, supporting teaching and learning practices across diverse contexts. Specific Background: This study explores technology use in schools across three Indonesian islands Sumatra, Kalimantan, and Sulawesi through a holistic review of 34 newspaper and online articles published between 2022 and 2024. Knowledge Gap: Previous studies have rarely utilized newspaper sources to examine region-specific technological issues in Indonesian education, particularly across multiple islands. Aims: The study aims to identify key issues and challenges associated with integrating technology into teaching and learning practices in these regions. Results: The findings reveal that limited infrastructure, including inadequate computers and slow internet access, remains a major challenge, especially in Kalimantan and Sulawesi, while more structured technological initiatives are evident in Sumatra; despite constraints, schools demonstrate adaptive strategies such as digital literacy programs, coding activities, and the use of simple technologies to support learning engagement. Novelty: The study introduces a holistic literature review approach based on newspaper data to map educational technology conditions across geographically diverse regions. Implications: The results highlight the need for collaborative support among schools, government, and private sectors, as well as the importance of preparing pre-service teachers to utilize low-bandwidth and simple technologies suitable for remote educational settings. Highlights• Limited infrastructure remains a central barrier in multiple regions• Rural classrooms adopt adaptive digital practices despite constraints• Teacher education requires focus on simple technology utilization KeywordsEducational Technology; Rural Education; Digital Infrastructure; Teacher Education; Indonesia